Characterization of the Microbiota Associated With 12-Week-Old Bovine Fetuses Exposed to Divergent in utero Nutrition - Amat, Samat; Holman, Devin B.; Schmidt, Kaycie; McCarthy, Kacie L.; Dorsam, Sheri T.; Ward, Alison K.; Borowicz, Pawel P.; Reynolds, Lawrence P.; Caton, Joel S.; Sedivec, Kevin K.; Dahlen, Carl R. (Frontiers in Microbiology, 2022)
A recent study reported the existence of a diverse microbiota in 5-to-7-month-old calf fetuses, suggesting that colonization of the bovine gut with so-called “pioneer” microbiota may begin during mid-gestation. In the present study, we investigated 1) the presence of microbiota in bovine fetuses at early gestation (12 weeks), and 2) whether the fetal microbiota is influenced by the maternal rate of gain or dietary supplementation with vitamins and minerals (VTM) during early gestation. Amniotic and allantoic fluids, and intestinal and placental (cotyledon) tissue samples obtained from fetuses (n = 33) on day 83 of gestation were processed for the assessment of fetal microbiota using 16S rRNA gene sequencing. The sequencing results revealed that a diverse and complex microbial community was present in each of these fetal compartments evaluated. Allantoic and amniotic fluids, and fetal intestinal and placenta microbiota each had distinctly different (0.047 ≥ R2 ≥ 0.019, P ≤ 0.031) microbial community structures. Allantoic fluid had a greater (P < 0.05) microbial richness (number of OTUs) (Mean 122) compared to amniotic fluid (84), intestine (63) and placenta (66). Microbial diversity (Shannon index) was similar for the intestinal and placental samples, and both were less diverse compared with fetal fluid microbiota (P < 0.05). Thirty-nine different archaeal and bacterial phyla were detected across all fetal samples, with Proteobacteria (55%), Firmicutes (16.2%), Actinobacteria (13.6%) and Bacteroidetes (5%) predominating. Among the 20 most relatively abundant bacterial genera, Acidovorax, Acinetobacter, Brucella, Corynebacterium, Enterococcus, Exiguobacterium and Stenotrophomonas differed by fetal sample type (P < 0.05). A total of 55 taxa were shared among the four different microbial communities. qPCR of bacteria in the intestine and placenta samples as well as scanning electron microscopy imaging of fetal fluids provided additional evidence for the presence of a microbiota in these samples. Minor effects of maternal rate of gain and VTM supplementation, and their interactions on microbial richness and composition were detected. Overall, the results of this study indicate that colonization with pioneer microbiota may occur during early gestation in bovine fetuses, and that that the maternal nutritional regime during gestation may influence the early fetal microbiota.